Implications of labor analgesia on labor outcomes – a systematic review - Tehalia, Manpreet Kaur; Agarwal, Shubhra; Lalwani, Astha (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Labor analgesia is a key component in ensuring maternal comfort during childbirth and impacts several maternal and neonatal outcomes. The selection of pharmacological and nonpharmacological analgesic methods significantly affects labor progression, delivery methods, neonatal health, and maternal satisfaction. This systematic review sought to assess the implications of labor analgesia on these outcomes by synthesizing evidence from various study designs. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Searches on the following electronic databases comprehensively: PubMed, Scopus, Web of Science, Cochrane Library, Embase, and CINAHL; Using Boolean operators and MeSH terms, six studies were included. These comprised randomized controlled trials, cohort studies, and observational studies that assessed maternal and newborn outcomes in the presence of labor analgesia. Data on types of analgesia, onset times, maternal hemodynamic outcomes, labor durations, delivery modes, neonatal Apgar scores, adverse events and maternal satisfaction were extracted. The exclusion criteria were studies that did not meet the inclusion criteria, such as reviews, editorials, and non-human studies. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. The analysis involved a wide range of studies employing analgesia methods such as epidural, com bined spinal-epidural (CSE), programmed intermittent epidural bolus (PIEB), and non-pharmacological interventions. Ropiva caine (0.1–0.2%) with fentanyl (7.5–25 µg/mL) was the most commonly used combination. The onset times ranged from imme diate to 200 minutes for prolonged durations of PIEB. Labor durations were variable. Some techniques, such as peripheral nerve blocks, reduced second stage labor by 33.8 minutes, whereas epidural analgesia prolonged labor duration in some cohorts. The modes of delivery outcomes were characterized by relatively minimal variations in cesarean rates between techniques, while operative vaginal deliveries were more likely with routine epidurals. Neonatal outcomes were otherwise favorable with nor mal Apgar scores, although some studies reported lower 1 minute Apgar scores with epidurals. Adverse events, such as motor blockade and postdural puncture headaches, were usually technique-dependent and minimal. Maternal satisfaction was high in all methods, with ultrasound-guided CSE, PIEB, and nonpharmacological methods receiving particularly positive feedback. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Labor analgesia showed overall safety and efficacy but varied impacts on labor duration, mode of delivery, and neonatal outcomes with the technique used. Although most of them had high maternal satisfaction and stable maternal he modynamics, some increased operative deliveries or adverse newborn outcomes. These results underscore the importance of tailoring analgesic strategies to individual clinical needs to optimize maternal and neonatal outcomes.